(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the didactic essence of non-standard laboratory work in physics teaching, its design methodology, and its role in the educational process. The structure of non-standard laboratory work (goal, means, result, assessment), its differences from traditional laboratory work, and the conditions for organizing it in accordance with didactic principles are described. Scientific and practical recommendations are provided.